A Method for Deriving Trip Destinations and Modes for GPS-based Travel Surveys - Wendy Bohte; Kees Maat; Wilko Quak (Research in Urbanism Series, 2008)
This chapter contributes to the improvement of GPS-based travel surveying by introducing a combined method of GPS, GIS and web-based user interaction, which has been applied in large- scale fieldwork in the netherlands. With over 1000 participants, as far as we know, this is the first time that a GPS-based method that measures travel mode choice as well as the location and type of destinations that are visited has been used on such a large scale. The chapter focuses in particular on the identification of travel modes and destinations, which is still an under-researched issue.